ePEARL: Electronic Portfolio Encouraging Active Reflection Learning - Wade, Anne; Abrami, Philip C.; Iolie Nicolaidou; Morris, K. (My University, 2006)
In Québec, like many other places, more than 20 percent of primary-school students have to repeat a grade before going on to secondary school and 70 percent of those drop out of high school (Statistics Canada, 2001). Currently, school is too often a place that disengages learners, which fails to encourage honest self-assessment, and where learning and evaluation are not meaningful acts of improvement but detached and punitive symbols of failure. Over the past several years, the Québec Ministère de l’Education du Loisir et du Sport (MELS) has been phasing in the Québec Education Program (QEP)-a complete reform of the curriculum favoring an integrated, comprehensive learner-centred approach to education based partly on a co-constructed, inquiry-based curriculum that responds to individual student needs and interests. The cross-curricular competencies, which have become central to the reform, are designed to ensure that the skills and knowledge being taught in our schools meet the changing demands of the 21st century workforce (Conference Board of Canada, 2001; MEQ, 2001). One way to meet this challenge appears to lie in the use of electronic portfolios which can be designed to support the process of students’ self-regulated learning. The value of portfolios for exhibiting evidence of learning has been well established and while the research and debate continue over the best vehicles or formats for portfolios, their use has become mandate in Canadian provinces such as Quebec as a means for capturing students’ metacognitive processes and evidence of learning. Social cognitive theorists like Bandura (1986) identify personal, behavioral and environmental factors as triadic processes which influence student performance. These processes underlie the self-regulatory processes which Zimmerman (2000) defines as forethought, performance or volitional control and self-reflection. The importance of developing self-regulating ability within students has been extensively researched for the past two decades and is believed to be essential to successful learning within schools and extending self-directed learning into adulthood (Boekaerts, 1999; Corno & Randi, 1999). Concordia University’s Center for the Study of Learning and Performance (CSLP) has identified the potential for portfolios to provide evidence of self-regulation as well as the potential for a an electronic portfolio tool to support and scaffold self-regulation (Wade, Abrami, & Sclater, 2005). As the research continues regarding the effects of portfolios in their various formats, the development of a tool which not only supports the development of a student’s portfolio but also of their self-regulative abilities provides opportunities for researching student outcomes in both arenas. This presentation will provide the theoretical background that guided the redesign of the CSLP’s bilingual, web-based electronic portfolio, now called ePEARL, along with some of the key features within the software.
Keywords: ePEARL; Electronic Portfolio Encouraging Active Reflection Learning; Electronic Portfolios`; Student Self-Regulation